Assessment of RAFT polymerization in the synthesis of crosslinked materials for energy storage - Tristão, Paulo (2014)
The synthesis and characterization of two different classes of polymer crosslinked materials, useful for energy storage and improving energy efficiency, is here studied. Products resulting from the encapsulation of phase change materials (PCM), which can be used for thermal energy storage/release, are considered as first case study. For this purpose, different kinds of PCM can be considered in the encapsulation process, namely renewable based PCM such as natural fatty acids (e.g. stearic/palmitic acids). The sulfur inverse-vulcanization process, producing materials with useful electrochemical properties, is considered as second case study. This latter process takes advantage of the excess of elemental sulfur that is generated in petroleum refining and allows the synthesis of sulfur-rich copolymers to be applied (e.g.) as active materials in lithium-sulfur (Li-S) batteries.